#### (i) 16^{3/4} + 2 (1/2)^{-1} (3)^{0}

#### (ii) (81)^{3/4} – (1/32)^{-2/5} + (8)^{1/3} (1/2)^{-1} (2)^{0}.

**Solution:**

(i) 16^{3/4} + 2 (1/2)^{-1} (3)^{0}

We can write it as

So we get

= (2)^{3} + 4

= 2 × 2 × 2 + 4

= 8 + 4

= 12

(ii) (81)^{3/4} – (1/32)^{-2/5} + (8)^{1/3} (1/2)^{-1} (2)^{0}

We can write it as

= 27 – 4 + 4

= 27

**More Solutions:**

- Evaluate for the following indices:
- Simplify for the following indices:
- Solve Indices:
- Solve the following : (i) (a-1 + b-1) ÷ (a-2 – b-2)
- Prove the following: (i) (a + b)-1 (a-1 + b-1) = 1/ab
- If a = cz, b = ax and c = by, prove that xyz = 1.
- Prove that aq – r. br – p. cp – q = 1.
- Prove that 1/x + 1/y + 1/z = 0.
- Prove that x = 2yz/y – z.